2009
DOI: 10.1002/ange.200904570
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and Palladium Silyl Pincer Complexes: Unusual Structural Rearrangements that Involve Reversible SiC(sp3) and SiC(sp2) Bond Activation

Abstract: Transition-metal pincer complexes have been the subject of numerous reactivity studies that range from explorations of catalytic activity to investigations of challenging bond-activation reactions. [1] With the goal of extending the versatility of metal pincer chemistry, significant effort has been devoted to the development of new pincer-like tridentate ligands by variation of the steric and electronic properties of the donor fragments and/or the ligand backbone. [1,2] In this context, pincer ligands that fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…A few recent examples include reports on complexes featuring PCP-, [4] PNP-, [5] and PSiP-type [6] pincer ligands, whereas Ni complexes featuring resorcinol-derived POCOP ligands have been shown to be prone to oxidative degradation. A few recent examples include reports on complexes featuring PCP-, [4] PNP-, [5] and PSiP-type [6] pincer ligands, whereas Ni complexes featuring resorcinol-derived POCOP ligands have been shown to be prone to oxidative degradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent examples include reports on complexes featuring PCP-, [4] PNP-, [5] and PSiP-type [6] pincer ligands, whereas Ni complexes featuring resorcinol-derived POCOP ligands have been shown to be prone to oxidative degradation. A few recent examples include reports on complexes featuring PCP-, [4] PNP-, [5] and PSiP-type [6] pincer ligands, whereas Ni complexes featuring resorcinol-derived POCOP ligands have been shown to be prone to oxidative degradation.…”
mentioning
confidence: 99%
“…In this context, there have been sporadic reports describing pincer complexes in which one or more binding moiety undergoes unexpected reactions that introduce major modifications in the pincer framework. A few recent examples include reports on complexes featuring PCP-, [4] PNP-, [5] and PSiP-type [6] pincer ligands, whereas Ni complexes featuring resorcinol-derived POCOP ligands have been shown to be prone to oxidative degradation. [7] Indeed, the aliphatic analogues of POCOP ligands, POC sp3 OP (Scheme 1), are particularly vulnerable to complex side reactions leading to decomposition.…”
mentioning
confidence: 99%
“…Although not common, the rupture of SiÀC bonds has already been documented under other circumstances. [35] The rhodium-catalysed coupling of 2-trimethylsilylphenylboronic acid with internal alkynes produces 2,3-disubstituted benzosilole derivatives. [33] More recently,s everal cases of metal-promoted SiÀCb ond ruptures have been disclosed for both C sp 2 and C sp 3 carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…[34] Nickel andp alladium silyl pincerc omplexes can undergo structural rearrangements implicating reversible SiÀC sp 3 and SiÀC sp 2 bond activation. [35] The rhodium-catalysed coupling of 2-trimethylsilylphenylboronic acid with internal alkynes produces 2,3-disubstituted benzosilole derivatives. [36] 2 SiMeR (R = Ph, Me, Et);i tw as shown that the facility of bond activation increased with temperature and according to SiÀEt < SiÀMe < SiÀPh.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, pincer ligands with two phosphine donors and a central anionic Si donor (PSiP ligands) have attracted attention owing to the high trans influence of the Si atom and the rigidity of the pincer framework 7. Turculet and co‐workers have demonstrated that complexes supported by this ligand can undergo reversible SiC bond cleavage,7f whereas Takaya and Iwasawa utilized catalysts with PSiP ligands for the carboxylation of allenes under mild conditions 7d. Complexes supported by the PSiP ligand have not only given rise to interesting reactivity but have also led to the formation of structurally remarkable species.…”
Section: Methodsmentioning
confidence: 99%